The association between coagulopathies such as thrombophilia or rare bleeding disorders with the development of gestational vascular complications. (December 2020) - Santamaría, Amparo
Abstract : N/A: The association between coagulopathies, more specifically thrombophilia, and the development of gestational vascular complications was established in the 1990s. Ever since, huge efforts have been invested into gaining a better understanding of the role played by clotting factors, both prothrombotic and hemorrhagic, in those complications, not least because hypertensive disorders and venous thromboembolism are among the most common causes of maternal mortality in the Western world.